2022
DOI: 10.1007/s13313-021-00847-4
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variability in populations of Chrysoporthe cubensis and Chr. puriensis in Brazil

Abstract: Chrysoporthe puriensis, a sibling species of the well-known Eucalyptus canker pathogen Chr. cubensis, has recently been described from Brazil. Both species are thought to be native to South America, but previous population genetic analyses were conducted prior to the ready availability of robust markers such as microsatellites to test this hypothesis. The objective of this investigation was to analyse the structure and genetic variability of Chr. cubensis and Chr. puriensis populations from non-native Myrtacea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 61 publications
2
15
0
Order By: Relevance
“…remain plausible candidates for the native hosts of C . deuterocubensis in Asia and this would be consistent with the study of Oliveira et al (2022) who showed clear evidence of a Melastoma sp. in Brazil as a native host of both C. cubensis and C. puriensis .…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…remain plausible candidates for the native hosts of C . deuterocubensis in Asia and this would be consistent with the study of Oliveira et al (2022) who showed clear evidence of a Melastoma sp. in Brazil as a native host of both C. cubensis and C. puriensis .…”
Section: Discussionsupporting
confidence: 93%
“…The same sub‐clades for isolates of C . deuterocubensis have also been noted in previous studies (Myburg, Gryzenhout, Heath, et al, 2002; Oliveira et al, 2022). It is not unusual of find such differences in gene regions for a single species, especially where the populations are large (Milgroom, 1996 ), and we believe that it is reasonable to treat the isolates used in this study as those of C. deuterocubensis .…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations